Contributions to Networked and Event-Triggered Control of Linear Systems - Guinaldo Losada, María; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reports on a set of new techniques for resolving current issues in networked control systems. The main focus is on strategies for event-based control, for both centralized and decentralized architectures. The first part of the book addresses the problem of single-loop networked control systems and proposes an anticipative remote controller for dealing with delays and packet losses. The second part of the book proposes a distributed event-based control strategy for networked dynamical systems, which has been implemented in a test-bed of mobile robots, and provides readers with a thorough description of an interactive simulator used to validate the results. This thesis, examined at the Universidad Nacional de Educación a Distancia in 2013, received the award for best thesis in controlengineering from the Control Engineering group of the Spanish Committee of Automatic Control in 2015.
Introduction -- Anticipative Control Design in Internet-like Networks -- Implementation and Experimental Evaluation of the Anticipative Control -- Distributed Event-Based Control for Interconnected Linear Systems -- Extensions and Improvements of the Distributed Event-Based Control.-Simulation Tools and Application Example of the DEBC: Networked Mobile Robots -- Conclusions and Future Work -- Proofs.
Keywords: Control engineering; Computer networks .; Telecommunication; Control and Systems Theory; Computer Communication Networks; Communications Engineering, Networks